2021
DOI: 10.1021/acsphotonics.1c00257
|View full text |Cite
|
Sign up to set email alerts
|

40 × 40 Metalens Array for Improved Silicon Photomultiplier Performance

Abstract: The photon detection efficiency (PDE) and timing performance of silicon photomultipliers (SiPMs) need to be improved for various applications, including time-of-flight positron emission tomography, light detection and ranging, and high-energy physics experiments. However, the irradiation of some incident photons to the low-photosensitivity areas of the SiPM negatively affects its PDE and timing performance. In this study, we developed a 40 × 40 metalens array to focus incident photons on the photosensitive are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Nevertheless, despite the limitation due to the indirect bandgap of bulk MoS 2 , the pronounced dielectric resonances and self-coupled polaritons demonstrated in this work indicate the great potential of adopting the CVD bottom-up method for dielectric metaphotonics and engineering light-matter interaction. The bottom-up strategy introduced in this work provides additional design flexibility for photonic devices, rendering it a promising way to realize large-area metasurfaces 35 , 53 with vdW TMDC materials.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite the limitation due to the indirect bandgap of bulk MoS 2 , the pronounced dielectric resonances and self-coupled polaritons demonstrated in this work indicate the great potential of adopting the CVD bottom-up method for dielectric metaphotonics and engineering light-matter interaction. The bottom-up strategy introduced in this work provides additional design flexibility for photonic devices, rendering it a promising way to realize large-area metasurfaces 35 , 53 with vdW TMDC materials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the improvement in the PDE of the metalens‐integrated SiPM was maintained up to an incident angle of 45°; in contrast, even a SiPM tilt angle of 6° from our previous report significantly displaces the focal point, which leads to PDE degradation since the metalens and the SPAD were separated by 200 μm. [ 21 ] In this study, we suppressed this displacement by directly fabricating the metalens on top of thin silicon dioxide (with a thickness of approximately 6.5 μm) on the SiPM, which reduces the distance between the metalens and the SiPM. As a result, we achieved PDE improvement using this method toward an oblique incident angle of up to 45°.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these advantages, we introduce a monolithic metalens integrated with SPAD rather than using microlenses.Our previous study demonstrated that metalenses can improve the PDE and timing performance of the SiPM by focusing the incident photons toward the photosensitive area of the SPAD while avoiding illumination to the trench area. [21] However, as the metalens and SiPM are spatially separated, it is difficult to fix the relative position (e.g., tilt, distance, and alignment) between the metalens and the SiPM. Thus, a separate configuration is not practical.…”
mentioning
confidence: 99%
“…5(a), the solar radiation covers the ultra-broad bandwidths from the NIR region (from 780 nm to 2526 nm) to the deep-UV (DUV) range (from 190 nm to 280 nm) [18,176,177]. According to the aforementioned introduction of the building materials, a meta-lens that is formed using different materials generally operates at the corresponding spectrum, and thereby, we will introduce the high-focusing-efficiency optical meta-lenses in terms of their working wavelengths, including the NIR [169,174,[178][179][180][181][182], visible [134,152,164,165,[183][184][185][186][187], and UV bands [146,148,149,[188][189][190][191][192][193]. The focusing efficiency is defined as the optical power confined within a focal spot divided by the corresponding incident power.…”
Section: Focusing Efficiencymentioning
confidence: 99%